Contextualizing Disengagement: How Exit Barriers Shape the Pathways Out of Far-Right Extremism in the United States. (4th March 2023) - Jensen, Michael; James, Patrick; Yates, Elizabeth
Abstract: This paper explores how obstacles to disengagement and push and pull factors combine to produce pathways out of extremism. Using Qualitative Comparative Analysis and a sample of 50 far-right extremists in the United States, including 25 who disengaged and 25 who did not, we show how certain exit barriers, like the presence of extremist family members, poor social mobility, and past criminal convictions, determine which push and pull factors are capable of assisting individuals in leaving extremism. We conclude with how these findings can be used to support intervention and reintegration programs.